A Generalized Visual Aid System for Teleoperation Applied to Satellite Servicing. (27th February 2014) - Zhang, Guoliang; Wang, Zhanni; Du, Jixiang; Wang, Tian; Jiang, Zainan
This paper presents the latest results of a newly developed visual aid system for direct teleoperation. This method is extended to visual control to make an efficient teleoperation system by combining direct teleoperation and automatic control. On the one hand, an operator can conduct direct teleoperation with 3D graphic prediction simulation established by the VR technique. In order to remove inconsistencies between the virtual and real environments, a practical model-matching method is investigated. On the other hand, to realize real-time visual servoing control, a particular object recognition and pose estimation algorithm based on polygonal approximation is investigated to ensure a low computational cost for image processing. To avoid undesired forces involved in contact operation, 3D visual servoing incorporating a compliant control based on impedance control is developed. Finally, in a representative laboratory environment, a typical satellite servicing experiment is carried out based on this combined system. Experimental results demonstrate the feasibility and the effectiveness of the proposed method.